PERUBAHAN STRUKTUR DAN KEPADATAN TRIKOMATA NON GLANDULER SERTA LUAS DAUN KAKAO (Theobroma cacao L.) PADA PERLAKUAN STRES KEKURANGAN AIR - Prihastanti, Erma; T, Soekisman; Soepandi, Didie; Qayim, Ibnul (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT--Cacao  is the one  important  crop in Indonesia. Water  stress  is perhaps  the major factor  limiting  crop growth. Plant responses to water stress  include morphological of biochemical changes. This reserch was aimed studying  strtructure and density of non glanduler  trichomes, and leaf area on cacao leaves on drought experiment.  The drought studies used throughfall displacment experiment  (TDE). The result show that cacao leaves have non glanduler trichomes type stellat. Non Glanduler trichomes were distributed throughtout the vein of leaves with distribution in abaxial parts of the leaves. TDE give non significant effect to trichomes density and Ieaf area. The highest trichomes  happened  on March 2008  6.9861/cm2. Leaf area on shade Ieaves  (273,56 cm2) more higher than sun leaves  (235,50 cm2). Keyword : Trichomes  non  glanduler, cacao leaves, leaf area